2019
DOI: 10.1136/bmj.l6459
|View full text |Cite
|
Sign up to set email alerts
|

Does general anesthesia affect neurodevelopment in infants and children?

Abstract: General anesthesia has been unequivocally linked to abnormal development of the central nervous system, leading to neurocognitive impairments in laboratory models. In vitro and in vivo studies have consistently shown that exposure to GABA agonists (eg, volatile anesthetics, midazolam, and propofol) or NMDA antagonists (eg, ketamine, isoflurane, and nitrous oxide) produces dose dependent and developmental age dependent effects on various neuronal transmission systems. Exposure to these drugs increases neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 105 publications
(114 reference statements)
1
95
1
8
Order By: Relevance
“…There is considerable interest and some concern over the potential risk of general anesthesia, volatile anesthetics in particular, on the developing brain [1][2][3][4]. This potential for neurocognitive effects led the Food and Drug Administration (FDA) to release a Safety Statement in 2017, approving label changes for general anesthetics in young children.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest and some concern over the potential risk of general anesthesia, volatile anesthetics in particular, on the developing brain [1][2][3][4]. This potential for neurocognitive effects led the Food and Drug Administration (FDA) to release a Safety Statement in 2017, approving label changes for general anesthetics in young children.…”
Section: Introductionmentioning
confidence: 99%
“…A preponderance of basic science and animal model studies [43][44][45][46] have demonstrated the neurotoxic and neurological effects of commonly used medications for moderate sedation and general anesthesia. Ongoing clinical trials 21,25 have not supported an association between single anesthetic exposure and general intelligence or learning, but there is evidence suggesting that multiple exposures may decrease neuropsychological domains affecting executive functioning. 25,47 The US Food and Drug Administration approved a label change regarding possible neurotoxic effects of general anesthetic and sedation medications in children younger than 3 years, warning that "exposure to these medicines for lengthy periods of time or over multiple surgeries or procedures may negatively affect brain development in children younger than 3 years."…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing clinical trials 21,25 have not supported an association between single anesthetic exposure and general intelligence or learning, but there is evidence suggesting that multiple exposures may decrease neuropsychological domains affecting executive functioning. 25,47 The US Food and Drug Administration approved a label change regarding possible neurotoxic effects of general anesthetic and sedation medications in children younger than 3 years, warning that "exposure to these medicines for lengthy periods of time or over multiple surgeries or procedures may negatively affect brain development in children younger than 3 years." 20 Beyond potential adverse clinical outcomes, reducing dental surgical procedures has immediate financial implications for health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol is still an off-label choice in most clinical pediatric practices (Chidambaran et al, 2015). The current dilemma is that there is a lack of evidence to support the safe use of propofol and there are a growing number of pre-clinical studies attributing neurotoxicity and neurogenic impairment to propofol (Krzisch et al, 2013;Bosnjak et al, 2016;McCann and Soriano, 2019).…”
Section: Introductionmentioning
confidence: 99%